2019
DOI: 10.1002/ijc.32246
|View full text |Cite
|
Sign up to set email alerts
|

Targeting RIPK1 in AML cells carrying FLT3‐ITD

Abstract: Mutations of fms-like tyrosine kinase 3 (FLT3) are the most frequent mutations in acute myeloid leukemia (AML). Furthermore, the internal tandem duplication (ITD) represents the most common mutation of FLT3 in AML. To explore therapeutic strategies for AML patients carrying FLT3-ITD, we analyzed death receptor (DR) signaling networks in AML cells comprising FLT3-ITD. We have started with murine myeloid progenitor 32D cells that ectopically express human FLT3-ITD (32D-FLT3-ITD) and found that RIPK1 is strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…CHIP/STUB1 regulated necroptosis through ubiquitination and lysosomal-dependent degradation of RIPK1 and RIPK3 ( Tang et al, 2018 ). In addition, RIPK1 in the myeloid progenitor with FLT3 mutations had a strongly increasing tendency ( Hillert et al, 2019 ). Furthermore, we established a nomogram model for predicting the OS of KIRC patients in combination with NRGscore and several clinicopathological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…CHIP/STUB1 regulated necroptosis through ubiquitination and lysosomal-dependent degradation of RIPK1 and RIPK3 ( Tang et al, 2018 ). In addition, RIPK1 in the myeloid progenitor with FLT3 mutations had a strongly increasing tendency ( Hillert et al, 2019 ). Furthermore, we established a nomogram model for predicting the OS of KIRC patients in combination with NRGscore and several clinicopathological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal gene expression is closely related to tumor prognosis. Studies have shown that NPM1 (9), FLT3 (10,11), C-KIT (12), AML1-ETO (13), RUNX1 (3,14), TP53 (3,15), CBFB/MYH11 (13,16), TET2 (17), DNMT3A (18), JAK-STAT (19), and CXCR4 (20,21) ,HOXA family (22), NAT10 (23) gene are associated with prognosis of AML. A few studies have shown altered DNA methylation in cancer, but the roles of key differentially methylated genes (DMGs) and differentially expressed genes (DEGs) in AML remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al demonstrated that the overexpression of lncRNA CASC7 increased the FASLG expression and promoted apoptosis of BC cells [36]. FLT3 is the most common mutation site in acute myeloid leukemia, and the mutation of FLT3 increased the expression level of RIPK1 and the sensitivities of necroptosis [37]. Recent studies indicated that zinc transporter SLC39A7 participated in regulating TNFR1-mediated necroptosis and activated endoplasmic reticulum stress in cells [38].…”
Section: Discussionmentioning
confidence: 99%